(untitled) (Research, Society and Development, 2020)
The aim of this study was to determine whether the addition of a homeopathic product to dairy cow feed would improve health and production efficiency, as well as composition and quality of milk. The product tested here was produced to stimulate immunity and indirectly to prevent the colonization of the mammary gland by bacteria, thereby decreasing somatic cell counts and bacteria in cow’s milk. Fifty dairy cows were used, divided into two groups: Control (n = 25) and Treated (n = 25). For 90 consecutive days, 50 grams of homeopathic product (treated group) was added to the concentrate; 50 g of the product vehicle (limestone) was added to the concentrate of the control cows. We performed composition and quality analysis on the milk (days 1, 15, 30, 45, 60, 75, and 90) as well as blood collection to carry out hematological and metabolism analyses (days 1, 30, 60, and 90). We found that fat content in the milk cows consuming the homeopathic agent was greater than that of the control group. Because of this increased fat content, there was a tendency towards higher total solids content in treated cows. A treatment effect was found in terms of total bacterial count (TBC); that is, there were lower TBCs in milk of treated animals than in control animals. There was a trend of a treatment effect versus day for somatic cell count (SCC); that is, there were lower SCC in animals that consumed the homeopathic on days 15 and 30 of the experiment. There was no difference between groups in terms of milk production; however, there was a negative correlation between milk production and TBC or SCC in the milk of cows that consumed homeopathic product. Animals in the treated group had lower total leukocyte and lymphocyte counts than did the control group, as well as a tendency toward lower neutrophil counts in these animals. Several bacteria were isolated from the cows’ milk during the experimental period, with no treatment effect. In particular, we isolated Corynebacterium spp., Staphylococcus aureus, Staphylococcus epidermidis and Staphylococcus hyicus in greater numbers of cows compared to other etiologic agents. Based on these results, we conclude that consumption of the homeopathic product by dairy cows had positive effects on milk quality.